2012
DOI: 10.1039/c1dt11404b
|View full text |Cite
|
Sign up to set email alerts
|

Chelating alkylidene ligands as pacifiers for ruthenium catalysed olefinmetathesis

Abstract: Olefin metathesis catalysed by ruthenium has emerged at the frontier of modern synthetic chemistry. The desire to enhance catalyst stability, gain control over the catalytic process and deepen the understanding of the mechanisms of metathesis has yielded a class of latent ruthenium precatalysts of delayed initiation and with switchable activity. One of the main methodologies developed for this purpose has been the introduction of tethered carbene ligands. Herein we track the evolution of ruthenium based metath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 90 publications
1
56
0
Order By: Relevance
“…Although most of the existing literature supports the trans coordination mode (demonstrated for the Grubbs II system B [42,43]), both pathways may exist depending on the type of ligand and nature of the olefin. Indeed, since 2000, several studies have tried to reveal the preference for the trans mode and/or find alternative ways to promote the cis mode [44,45]: the issue remains an open debate in NHC-ruthenium catalysis [46,47]. In summary, a trans binding preferential can be generally postulated, but the special nature of the present phosphine-phosphonium ylide ligand might provide an example where the olefin can be coordinated in the cis mode: Correa and Cavallo [48] indeed showed that the trans/cis selectivity was based on a delicate balance between steric and electronic effects, also depending on the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Although most of the existing literature supports the trans coordination mode (demonstrated for the Grubbs II system B [42,43]), both pathways may exist depending on the type of ligand and nature of the olefin. Indeed, since 2000, several studies have tried to reveal the preference for the trans mode and/or find alternative ways to promote the cis mode [44,45]: the issue remains an open debate in NHC-ruthenium catalysis [46,47]. In summary, a trans binding preferential can be generally postulated, but the special nature of the present phosphine-phosphonium ylide ligand might provide an example where the olefin can be coordinated in the cis mode: Correa and Cavallo [48] indeed showed that the trans/cis selectivity was based on a delicate balance between steric and electronic effects, also depending on the solvent.…”
Section: Resultsmentioning
confidence: 99%
“…These cisdichloro complexes are generally characterized by a latent behavior, meaning that they are catalytically inactive at ambient temperatures, but develop their activity at higher temperatures. This feature can be of particular interest in industrial processes where regulation of the initiation is crucial for the operational control [15,16], e.g., in reactive injection molding (RIM) of strained cyclic olefins which are polymerized by ring-opening metathesis polymerization (ROMP) [17,18]. Also, cis-dichloro catalysts outperform their trans-dichloro counterparts in several metathesis transformations which demand high temperature [14,19,20].…”
Section: Introductionmentioning
confidence: 98%
“…A particular precedentsetting example is the second-generation Hoveyda complex [3], bearing a chelating 2-(isopropoxy)benzylidene moiety. Numerous structural modifications of the parent compound were described in literature, and the changes concerned essentially the whole coordination sphere around the ruthenium center, namely the N-heterocyclic carbene, the anionic ligands, and the chelating benzylidene moiety [4][5][6]. In the latter case, altering the electronics of the benzylidene (i.e., introducing electron-withdrawing or-& Christian Slugovc slugovc@tugraz.at donating substituents) and changing the chelating heteroatom in ortho position to the carbene constitute the most important strategies to adjust the catalytic properties of this compound class [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous structural modifications of the parent compound were described in literature, and the changes concerned essentially the whole coordination sphere around the ruthenium center, namely the N-heterocyclic carbene, the anionic ligands, and the chelating benzylidene moiety [4][5][6]. In the latter case, altering the electronics of the benzylidene (i.e., introducing electron-withdrawing or-& Christian Slugovc slugovc@tugraz.at donating substituents) and changing the chelating heteroatom in ortho position to the carbene constitute the most important strategies to adjust the catalytic properties of this compound class [4][5][6]. Please keep in mind that only the initiation step can be influenced by such modifications (at least when neglecting the controversially discussed Boomerang effect [7][8][9]).…”
Section: Introductionmentioning
confidence: 99%